Effect of pre-treatment on the quality of carbon-infiltrated bio-char - Zulkefli, Farah Dzilhani; Rozhan, Alya Naili; Mohd. Salleh, Hamzah; Purwanto, Hadi (Kuala Lumpur, Malaysia, 2016)
Pyrolysis process of biomass produces tar that caused clogging of equipment in industry. A process is proposed to recover by infiltrating the tar vapor within porous bio-char and then carbon deposition occurred on the pore surface by chemical vapor infiltration process. This work focuses on investigation of the effect of EFB pre-treatment on the quality of carbon infiltrated bio-char product. In this experiment, porous bio-char pellets were produced by slowly heating of EFB pellets in a tube furnace under argon atmosphere at temperatures of 400°C - 800°C. In the second step, the porous bio-char pellets were used as substrate for tar decomposition process to deposit carbon within the bio-char pores. Tar vapor was obtained from the pyrolysis of treated and untreated EFB at 450°C with heating rate of 100°C/min. The tar vapor produced was then infiltrated into porous bio-char followed by decomposition. The result shows that treatment of EFB by washing and drying to produce tar vapor leads to increment of carbon content within bio-char. This treatment also enhanced the calorific value of bio-char to 6,843 kcal/kg. The product could be used as an alternative energy source to substitute the present fossil fuel such as metallurgical coke in industry in order to contribute in mitigation of global warning